1994
DOI: 10.1177/875687059401300206
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Rural Students1Attitudes Toward Peers with Disabilities: A Comparison of Interventions

Abstract: This study investigated the impact of two widely used commercial programs designed to increase peer understanding and acceptance of elementary school-aged handicapped students. Second, fourth, and sixth graders from six rural school districts were used in the study. The Better Understanding of Disabled Youth (BUDY) program and the Lets Meet the New Kids on the Block (KOB) program were two treatments employed to determine whether positive gains in attitudes toward the disabled could be systematically attained. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Four studies were conducted in Canada and 21 studies were conducted in the United States. Ten studies were published in peer-reviewed journals (Baker, Rude, Sasso, & Weishahn, 1994;Binkard, 1985;Dunst, 2012;Gilfoyle & Gliner, 1985;Rosenbaum et al, 1986b;Snart & Maguire, 1986, 1987, whereas the other studies were reported either in dissertation or master theses (Baker, 1991;Illmann, 1990;Johnson, 1998;Powell, 1985;Russell, 1993;Schumacher, 1998;Thorton-Biddle, 1983;Zucker, 1988) or were conference presentations or unpublished articles (Anderson, Del-Val, Griffin, & McDonald, 1983;Chase, Lebewohl, Mulcahy, & Shiffer, 1983;PACER Center, 1986;Pendzick, 1983).…”
Section: Searc H Results Smentioning
confidence: 99%
“…Four studies were conducted in Canada and 21 studies were conducted in the United States. Ten studies were published in peer-reviewed journals (Baker, Rude, Sasso, & Weishahn, 1994;Binkard, 1985;Dunst, 2012;Gilfoyle & Gliner, 1985;Rosenbaum et al, 1986b;Snart & Maguire, 1986, 1987, whereas the other studies were reported either in dissertation or master theses (Baker, 1991;Illmann, 1990;Johnson, 1998;Powell, 1985;Russell, 1993;Schumacher, 1998;Thorton-Biddle, 1983;Zucker, 1988) or were conference presentations or unpublished articles (Anderson, Del-Val, Griffin, & McDonald, 1983;Chase, Lebewohl, Mulcahy, & Shiffer, 1983;PACER Center, 1986;Pendzick, 1983).…”
Section: Searc H Results Smentioning
confidence: 99%
“…Throughout the 1980s, there was a popular program designed to change the attitudes of nondisabled children toward those with disabilities called Kids on the Block (KOB; Aiello, 1980). KOB is a puppet show designed to provide positive information about persons with disabilities (Baker, Rude, Sasso, & Weishahn, 1994 (Greene & Shane, 1994). Therefore, KOB and facilitated communication appear to have at least this feature in common: They use props in an effort to change the way people think and feel about disabilities.…”
Section: Postmodernism In Special Educationmentioning
confidence: 99%